2019
DOI: 10.1186/s12909-019-1634-7
|View full text |Cite
|
Sign up to set email alerts
|

On-call transthoracic echocardiographic interpretation by first year cardiology fellows: comparison with attending cardiologists

Abstract: Background Transthoracic echocardiograms (TTE) performed and interpreted by cardiology fellows during off-duty hours are critical to patient care, however limited data exist on their interpretive accuracy. Our aims were to determine the discordance rate between TTEs performed and interpreted by cardiology fellows and National Board of Echocardiography certified attending cardiologists and to identify factors associated with discordance. Methods Consecutive on-call TTEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…When performed by humans, echocardiography and its measurements are subjective and greatly influenced by the level of expertise [ 5 , 10 ]. Since its first description there have been concerns about the reproducibility of LVEF due to significant intra-observer, inter-observer, and inter-institutional variability of measurements [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When performed by humans, echocardiography and its measurements are subjective and greatly influenced by the level of expertise [ 5 , 10 ]. Since its first description there have been concerns about the reproducibility of LVEF due to significant intra-observer, inter-observer, and inter-institutional variability of measurements [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, calculation of LVEF is strongly dependent both on image quality and on the experience of the reader [4]. Thus calculation of LVEF by non-cardiologists and beginners is a significant limitation for the widespread application of this parameter [5].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive exposure to the assessment of LV function is a difficult task that requires evaluation of a large number of patients. Indeed, even among cardiology trainees, the most frequent source of disagreement with attending overread is regarding LV function (19). This program took trainees less than 1 hour in total time and allowed trainees to be exposed to almost 100 exams of the LV in much less time than real-time examination of 100 patients by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study completed at Beth Israel demonstrated that in transthoracic echocardiogram interpretation there was a nearly 20% discrepancy rate (4.1% major and 17.4% minor) between cardiologists and the first-year cardiology fellows. 16 …”
Section: Discussionmentioning
confidence: 99%